Dendritic Cell-Based Immunotherapy for Prostate Cancer. (4th November 2010) - Jähnisch, Hanka; Füssel, Susanne; Kiessling, Andrea; Wehner, Rebekka; Zastrow, Stefan; Bachmann, Michael; Rieber, Ernst Peter; Wirth, Manfred P.; Schmitz, Marc
Abstract : Dendritic cells (DCs) are professional antigen-presenting cells (APCs), which display an extraordinary capacity to induce, sustain, and regulate T-cell responses providing the opportunity of DC-based cancer vaccination strategies. Thus, clinical trials enrolling prostate cancer patients were conducted, which were based on the administration of DCs loaded with tumor-associated antigens. These clinical trials revealed that DC-based immunotherapeutic strategies represent safe and feasible concepts for the induction of immunological and clinical responses in prostate cancer patients. In this context, the administration of the vaccine sipuleucel-T consisting of autologous peripheral blood mononuclear cells including APCs, which were pre-exposed in vitro to the fusion protein PA2024, resulted in a prolonged overall survival among patients with metastatic castration-resistent prostate cancer. In April 2010, sipuleucel-T was approved by the United States Food and Drug Administration for prostate cancer therapy.